Bio-inspired nacre-like composites with excellent mechanical properties, gas-barrier function and fire-retardant performances based on self-assembly between hyperbranched poly(amido amine)s and montmorillonite. Issue 6 (25th January 2023) - Jin, Biqiang; Wang, Hao; Xu, Hu; Wu, Haitao; Wu, Wenqiang; Yuan, Zhaoyang; Huang, Zhendong; Wang, Yinghan; Wu, Jinrong
Abstract : Nacre-like composites with excellent mechanical properties, gas-barrier function and fire-retardant performances are prepared by hyperbranched poly(amido amine)s and montmorillonite. Abstract : The fabrication of mechanically robust multifunctional nanocomposite (NC) films using simple but effective strategies is a long-term challenge. Inspired by natural nacre, we designed and fabricated high-performance nacre-like NC films (Na-MTM/HBP) through the self-assembly of the hyperbranched poly(amido amine) (HBP) and montmorillonite (Na-MTM) using a vacuum filtration approach. The optimal Na-MTM/HBP NC film shows excellent mechanical strength (106 MPa), which can be attributed to the formation of numerous hydrogen bonds and the electrostatic interactions between hyperbranched HBP and Na-MTM nanosheets. Such films also exhibit excellent gas barrier and fire–fire-retardant owing to the high aspect ratio of the Na-MTM nanosheets. In this work, a class of high-performance NC films exhibiting good mechanical, gas barrier, and flame retardancy properties have been developed. These NC films have great potential in packing or coating materials.